Validation of the name Aster veitchianus (Asteraceae) - Zhang, Guo-Jin; Zhang, Cai-Fei; Hu, Hai-Hua; Gao, Tian-Gang (Phytotaxa, 2013)
Aster veitchianus, a species endemic to western China, is widely accepted in taxonomic and phytochemical literature (e.g. Hu 1965, Li et al. 2007, Chen et al. 2011). However, its name was not validly published, because the original diagnosis given by Ling (1935: 214) was in French, not in Latin. Thus, Ling did not validate the name A. veitchianus according to Art. 39.1 of the ICN (McNeill et al. 2012). In our survey of the taxonomic literature, we have never found this name accompanied by a Latin diagnosis or description before 31 December 2011, nor by an English diagnosis or description after 1 January 2012. We herein provide an English description to accomplish valid publication of the name. The specimen X. B. Peng 6049 (Fig. 1) deposited in PE is designated as the holotype, which was the only one specimen cited by Ling (1935).